Shopping at Sales - Mary N. Harrison (EDIS)
Although there are many different kinds of sales, they all can be grouped into two general classifications: promotional and clearance. By recognizing the type of sale, a consumer is better able to anticipate the potential condition of merchandise and the amount of price reduction. This document is Fact Sheet FCS 5019, a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Revised: June 2005. First Published: April 1982.